Implementasi Pendekatan Culturally Responsive Teaching (CRT) pada Pembelajaran Lari Jarak Pendek Kelas 10 SMA N 2 Semarang - Mahfudz, Imam; Zhannisa, Utvi Hinda; Waskito, Tutur Lukas (Universitas PGRI Semarang, 2025)
This study aims to test the implementation of the CRT Culturally Responsive Teaching approach in the 10th grade of SMA N 2 Semarang. The research used is a Class Action Research. This research will be carried out at SMA N 2 Semarang and will involve students in grades X-11 as research subjects. Therefore, the population in this study is 36 students in grades X-11. This research took place from October 1 to October 17, 2024 which took place at SMA N 2 Semarang. The data collection process was carried out by conducting an assessment in 3 meetings about short-distance running materials. The results of the study showed that at the first meeting the most was very good with 19 people, but there were still 3 people who were in the poor category. In the second meeting, there was an increase, namely 29 people included in the good category, but there was still 1 student who was included in the very poor category. Finally, in the third meeting, the most was obtained, namely 34 students in the good category and 2 students in the sufficient category. At the first meeting, most of them were included in the very good category, while 53%. Meanwhile, at the second meeting, most of them were in the good category of 80%. In the third meeting, most of them were included in the very good category as much as 94% of the total students. The conclusion of this study is that the use of the CRT Culturally Responsive Teaching approach has an impact on the learning of short-distance running students of Grade 10 SMA Negeri 2 Semarang. The results of learning to run short distances in Class X students of SMA Negeri 2 Semarang have experienced a significant increase. In the first meeting, classical completeness in class X students was 89%, then increased by 3% in the second meeting. In the second meeting it got a score of 92% then increased by 2% in the third meeting to 94%. The suggestion for teachers of physical education, sports and health should be to provide guidance with an approach according to the cultural conditions of students so that students' enthusiasm and enthusiasm in learning are easy to understand.